RELIABILITY AND VALIDITY OF AN ACCELEROMETRIC SYSTEM FOR ASSESSING VERTICAL JUMPING PERFORMANCE - M.-A. Choukou; G. Laffaye; R. Taiar (Termedia Publishing House, 2014)
The validity of an accelerometric system (Myotest©) for assessing vertical jump height, vertical force and power, leg stiffness and reactivity index was examined. 20 healthy males performed 3×"5 hops in place", 3×"1 squat jump" and 3× "1 countermovement jump" during 2 test-retest sessions. The variables were simultaneously assessed using an accelerometer and a force platform at a frequency of 0.5 and 1 kHz, respectively. Both reliability and validity of the accelerometric system were studied. No significant differences between test and retest data were found (p<0.05), showing a high level of reliability. Besides, moderate to high intraclass correlation coefficients (ICCs) (from 0.74 to 0.96) were obtained for all variables whereas weak to moderate ICCs (from 0.29 to 0.79) were obtained for force and power during the countermovement jump. With regards to validity, the difference between the two devices was not significant for 5 hops in place height (1.8 cm), force during squat (-1.4 N · kg-1) and countermovement (0.1 N · kg-1) jumps, leg stiffness (7.8 kN · m-1) and reactivity index (0.4). So, the measurements of these variables with this accelerometer are valid, which is not the case for the other variables. The main causes of non-validity for velocity, power and contact time assessment are temporal biases of the takeoff and touchdown moments detection.